Peningkatan Mutu Satuan Kelompok Bermain Melalui Pembimbing Akreditasi - Muhammad Akil Musi; A. Sri Wahyuni Asti; Rusmayadi; Muhammad Yusri Bactiar; Azizah Amal; Sitti Nurhidayah Ilyas (Ininnawa : Jurnal Pengabdian Masyarakat, 2023)
This accreditation guidance activity is carried out based on an analysis of situations and problems found where the perception of educators and PAUD unit education staff is still low on the implementation of accreditation. This mentoring activity was carried out for one day at the An Nur Khaeriyah Playgroup located in Tanete Rilau District, Barru Regency, South Sulawesi Province. The methods used in this mentoring activity are counseling, discussion and question and answer, as well as practice and assignment. The participants involved in this activity were one manager and 3 educators. Based on the results and discussion, it can be concluded that participants can absorb the material well and can know and understand all the material delivered by the supervisor. The success of mentoring activities cannot be separated from the strong desire of educators and education staff as well as discipline during mentoring activities. The reflection of this mentoring activity is that participants in general can absorb the material well, but there are still some things that need to be improved, especially in the aspect of implementing STPPA indicators.